Propuesta de implementación paso 1, de mantenimiento autónomo en la maquina resortera fides MDC - 80 en americana de colchones (2022)
Americana de colchones is a company with more than 45 years of experience in the market, it is a company that started from the core of a Bogota family, which has been growing over the last few years, consolidating a single production plant located in Sopo Cundinamarca has 3 production areas within the plant (manufacturing, carpentry and metalworking) in the manufacturing area the mattress is built and finished, in the carpentry area the bed bases or bed bases are manufactured and in the metalworking area the spring units that support the mattress are manufactured, it is there where the MDC-80 spring machine is located, which is the Pareto equipment of the mattress production process, it is a machine with more than 20 years of operation, the equipment rarely It is intervened for preventive maintenance, since the production of springs is continuous and the production area has the time available, only corrective maintenance is carried out.